Imaging tools for plant nanobiotechnology - Zhao, Bin; Luo, Zhongxu; Zhang, Honglu; Zhang, Huan (Frontiers in Genome Editing, 2022)
The successful application of nanobiotechnology in biomedicine has greatly changed the traditional way of diagnosis and treating of disease, and is promising for revolutionizing the traditional plant nanobiotechnology. Over the past few years, nanobiotechnology has increasingly expanded into plant research area. Nanomaterials cannot just be used as vectors for targeted delivery and controlled release (such as fertilizers, pesticides, herbicides, nucleotides, proteins, etc.). Interestingly, nanomaterials with unique physical and chemical properties can directly affect plant growth and development; improve plant resistance to disease and stress; design as sensors in plant biology; and even be used for plant genetic engineering. Similarly, there have been concerns about the potential biological toxicity of nanomaterials. Selecting appropriate characterization methods will help understand how nanomaterials interact with plants and promote advances in plant nanobiotechnology. However, there are relatively few reviews of tools for characterizing nanomaterials in plant nanobiotechnology. In this review, we present relevant imaging tools that have been used in plant nanobiotechnology to monitor nanomaterial migration, interaction with and internalization into plants at three-dimensional lengths. Including: (i) Migration of nanomaterial into plant organs (ii) Penetration of nanomaterial into plant tissues（iii）Internalization of nanomaterials by plant cells and interactions with plant subcellular structures. We compare the advantages and disadvantages of current characterization tools and propose future optimal characterization methods for plant nanobiotechnology.